Galectin-3-independent Down-regulation of GABABR1 due to Treatment with Korean Herbal Extract HAD-B Reduces Proliferation of Human Colon Cancer Cells - Kim Kyung-Hee; Kwon Yong-Kyu; Cho Chong-Kwa; Lee Yeon-Weo; Lee So-Hyu; Jang Sang-Geu; Yoo Byong-Chu; Yoo Hwa-Seon (Korean Pharmacopuncture Institute, 2012)
Objectives: Many efforts have shown multi-oncologic roles of galectin-3 for cell proliferation, angiogenesis, and apoptosis. However, the mechanisms by which galectin-3 is involved in cell proliferation are not yet fully understood, especially in human colon cancer cells. Methods: To cluster genes showing positively or negatively correlated expression with galectin-3, we employed human colon cancer cell lines, SNU-61, SNU-81, SNU-769B, SNU-C4 and SNU-C5 in high-throughput gene expression profiling. Gene and protein expression levels were determined by using real-time quantitative polymerase chain reaction (PCR) and western blot analysis, respectively. The proliferation rate of human colon cancer cells was measured by using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results: Expression of γ-aminobutyric acid B receptor 1 (GABABR1) showed a positive correlation with galectin-3 at both the transcriptional and the translational levels. Downregulation of galectin-3 decreased not only GABABR1 expression but also the proliferation rate of human colon cancer cells. However, Korean herbal extract, HangAmDan-B (HAD-B), decreased expression of GABABR1 without any expressional change of galectin-3, and offset γ-aminobutyric acid (GABA)-enhanced human colon cancer cell proliferation. Conclusions: Our present study confirmed that GABABR1 expression was regulated by galectin-3. HAD-B induced galectin-3-independent down-regulation of GABABR1, which resulted in a decreased proliferation of human colon cancer cells. The therapeutic effect of HAD-B for the treatment of human colon cancer needs to be further validated.